A review of plume dispersion and measurement techniques applicable to marine cloud brightening - Hernandez-Jaramillo, Diana C.; Kelaher, Brendan; Harrison, Daniel P. (Frontiers in Marine Science, 2025)
Rising sea surface temperatures are causing more frequent and intense coral bleaching events, threatening the long-term survival of coral reefs globally. Marine Cloud Brightening (MCB) is a proposed intervention that could be applied globally or regionally to cool sea surface temperatures and reduce the risk and severity of coral bleaching. The effectiveness and logistical feasibility of this technique depends on what fraction of the sea salt aerosols are incorporated into clouds after being emitted from a seawater spraying operation at the ocean surface. Here, we review the literature on the dispersion of MCB sea salt aerosols from a point source within the marine boundary layer. We focus our consideration on the processes, mechanisms, and current ability to predict the horizontal and vertical evolution of the plume from its generation at surface level to its downwind dispersion and mixing to cloud height. Overall, we found that in the more than three decades since the MCB concept was first proposed there have been eight studies investigating this aspect of MCB, which is crucial to informing engineering systems design, marine logistics, and assessing the overall potential effectiveness of MCB. To date, only one study has validated the modeling of the aerosol dispersion using empirical experiments and only a few studies have considered non-passive processes such as the negative buoyancy associated with the evaporative cooling of the water droplets, as well as particle scavenging due to coagulation and deposition. Priority areas for future research are identified as far-field dispersion of the MCB plume and estimations of the portion of MCB aerosol reaching cloud base.